Different Dosage Forms Of Kwatha Kalpana: A Boon To Ayurveda Pharmaceutics - Amit Kumar Karna; Astha Ray; Kamal, Gopendra Chandra (Journal of Ayurveda Campus, 2025)
Background: The core concept of all the Ayurvedic dosage forms is laid upon Panchavidha kashaya kalpana (Five Basic Preparations) which are-1. Swarasa (Expressed juice), 2. Kalka (Paste), 3. Kwatha (Decoction), Hima (Cold infusion), Phanta (Hot infusion) respectively. Though Kwatha kalpana is one of the most described preparation for clinical practice and for secondary preparations as well, it is being used limitedly due the issues like Short shelf life, time required for preparation, unpalatability, transportation and storage etc. The Kwatha can be modified into different dosage forms like Arista, Tab/Capsule, Ghanavati, Pravahi kwath etc. keeping its therapeutic utility undisturbed much. Hence, the present attempt is made to introduce the different possible dosage forms of Kwatha kalpana. Materials and Methods: A descriptive and analytical review of Classical Ayurveda literatures like Charaka Samhita, Sharangadhara Samhita, and Yogaratnakara, Contemporary pharmaceutics texts and relevant scientific publications done. Results and Discussion: Study revealed that the Classical Kwatha with minimal selflife can be modified into other long-lasting formulations like Ghanavati, Granules, Tab/ Capsules, Syrup, Arishta and Pravahi Kwatha etc. without compromising its efficacy much. Major techniques involved for the conversion are drying, granulation, sweetening, and fermentation etc. Conclusion: Different dosage forms of Kwatha kalpana helps overcome the shortcomings of Kwatha like stability, standardization and patient compliance. Aligning the classical wisdom and contemporary techniques, we can build trust and serve ailing humanity in a better way.